Obesity and cancer: unravelling the microbiome’s hidden role - Gaskell, Christine; MacDonald, Ross; Aleem, Eiman; Bendriss, Ghizlane (Frontiers in Nutrition, 2025)
Obesity has been implicated as the driving force of many diseases including cancer through multiple biological mechanisms, including gut microbial imbalances, compromised intestinal barrier integrity, persistent low-grade inflammation, and alterations in energy uptake. As lifestyle factors such as diet, physical activity, and sleep are known to influence disease susceptibility, understanding the role of the gut microbiome in these interactions is critical. A deeper understanding of the intricate connections between gut microbiota, obesity, and various cancers could be used to better inform effective strategies for disease prevention and treatment. Investigating the microbiome’s influence on tumor progression and systemic metabolic health may be the way forward for novel diagnostic and therapeutic approaches. It is essential to investigate how lifestyle factors are linked to both obesity and cancer, and what role the microbiome is playing. This review synthesizes current research on the mechanistic role of the gut microbiome in obesity and cancer, highlighting its potential role in early detection, prognosis, and its use as a targeted intervention to restore gut eubiosis.